Asymmetric Adaptation of Deep Features for Cross-Domain Classification in Remote Sensing Imagery - Ammour, Nassim; Bashmal, Laila; Bazi, Yakoub; Al Rahhal, M. M.; Zuair, Mansour (IEEE geoscience and remote sensing letters, 2018)
In this letter, we introduce an asymmetric adaptation neural network (AANN) method for cross-domain classification in remote sensing images. Before the adaptation process, we feed the features obtained from a pretrained convolutional neural network to a denoising autoencoder (DAE) to perform dimensionality reduction. Then the first hidden layer of AANN (placed on the top of DAE) maps the labeled source data to the target space, while the subsequent layers control the separation between the available land-cover classes. To learn its weights, the network minimizes an objective function composed of two losses related to the distance between the source and target data distributions and class separation. The results of experiments conducted on six scenarios built from three benchmark scene remote sensing data sets (i.e., Merced, KSA, and AID data sets) are reported and discussed.